Managing suburban area using landscape evaluation and valorisation methods - Michał Łukowiak; Elżbieta Szopińska; Zbigniew Kuriata (Economic and Environmental Studies (E&ES), 2017)
Suburban zone is an extremely conflicted area exposed to very dynamic changes. Popularity of the suburbs increases every year. The rapid increase of population density and net migration from cities to rural areas changes the spatial, aesthetic and social character of these areas. Hence, it is a very important task to manage the suburban areas and to adequate planning for the environmental protection and development. A tool that can be used for this purpose is the landscape valorization. There are many methods of landscape valorization, therefore, they should be used skillfully by selecting the most important elements and rejecting those that may unfavorably affect spatial evaluate, maintaining the most objective approach.
Keywords: Q01; R10; R30; 330; landscape; valorization; evaluation; suburban area; Wroc±aw; Europe